COSTA RICA: A STUDY ON SEXUAL HARASSMENT IN A PUBLIC UNIVERSITY STUDENT POPULATION AND ITS PERCEPTION OF THE HOMOPHOBIC ENVIRONMENT IN 2008 - Carvajal Orlich, Zaira (2009)
This article presents the results of a survey administered between October and November 2008 to a student sample from Universidad Nacional (UNA) in Costa Rica in order to know the prevalence of students (in terms of male and female percentage) that claim to have suffered some sort of manifestation of sexual harassment during their studies at Universidad Nacional. In addition, this paper explores the studied population´s perception of the homophobic environment at UNA.